1985
DOI: 10.1073/pnas.82.2.552
|View full text |Cite
|
Sign up to set email alerts
|

Murine monoclonal antibodies to the myelin-associated glycoprotein react with large granular lymphocytes of human blood.

Abstract: Monoclonal antibodies prepared to human myelin-associated glycoprotein were shown to react with a population of human peripheral blood mononuclear cells. The population is similar to the large granular lymphocytes or natural killer cells defined by antibody Leu 7 (also called HNK-1). The population also includes cells exhibiting the Leu 2 marker for suppressor/cytotoxic T cells. The results indicate a shared antigenicity between the nervous system and the immune system and may be relevant to the pathogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

1986
1986
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…Noteworthy in this regard, monoclonal antibodies binding to polypeptide epitopes of the MAG glycoprotein lack immunoreactivity with human mononuclear cells reactive with HNK-1, whereas monoclonal antibodies directed against the sugar moiety of MAG react with the HNK-1+ granular lymphocytes (24). However, we observed that an antiserum reacting with the peptidic moiety of MAG, but that does not detect its HNK-1-defined carbohydrate antigenic determinant, still binds two membrane components from HNK-1+ thymocytes.…”
Section: Hnk-i/nc-i Antibody Reactivity In the Quail Thymus Andcontrasting
confidence: 48%
“…Noteworthy in this regard, monoclonal antibodies binding to polypeptide epitopes of the MAG glycoprotein lack immunoreactivity with human mononuclear cells reactive with HNK-1, whereas monoclonal antibodies directed against the sugar moiety of MAG react with the HNK-1+ granular lymphocytes (24). However, we observed that an antiserum reacting with the peptidic moiety of MAG, but that does not detect its HNK-1-defined carbohydrate antigenic determinant, still binds two membrane components from HNK-1+ thymocytes.…”
Section: Hnk-i/nc-i Antibody Reactivity In the Quail Thymus Andcontrasting
confidence: 48%
“…The results also demonstrate that the anti-melanoma antibodies (lOC5 and 1 lB5), like HNK-1, belong to a family of monoclonal antibodies that bind to carbohydrate determinants present in MAG, 19-28K-dalton glycoproteins of the PNS, and some sulfated, glucuronic acid-containing sphingoglycolipids of the PNS. A large number of mouse monoclonal antibodies raised in response to human MAG, as well as HNK-1, also react with these glycoconjugates (Ilyas et al, 1984~;Inuzuka et al, 1984;Nobile-Orazio et al, 1984;Dobersen et al, 1985b;OShannessy et al, 1985). In addition, the similarity of the anti-melanoma antibodies with some of the anti-MAG monoclonal antibodies and HNK-1 has been shown by their ability to immunostain the same subset of human lymphocytes with natural killer function as HNK-1 (J. R. Harper, N. M. Varki, P. Minden, P. J.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the similarity of the anti-melanoma antibodies with some of the anti-MAG monoclonal antibodies and HNK-1 has been shown by their ability to immunostain the same subset of human lymphocytes with natural killer function as HNK-1 (J. R. Harper, N. M. Varki, P. Minden, P. J. Kelleher, and R. A. Reisfeld, manuscript in preparation;Dobersen et al, 1985~).…”
Section: Discussionmentioning
confidence: 99%
“…4). Recently, it has been reported that mouse monoclonal anti-human MAG antibodies also react with large granular lymphocytes or NK cells of human blood (25). Anti-HNK-1 has been thought to be one of the markers of human natural killer (NK) cells (20).…”
Section: Discussionmentioning
confidence: 99%